Small teaching everyday lessons from the science of learning - Lang, James M. (Jossey-Bass, a Wiley Brand, 2021)
"Small Teaching fills the gap in higher education literature between the primary research in cognitive theory and the classroom environment. While other books provide research without concrete examples or simply introduce radical theories that ultimately are not useful in the classroom, this book offers simple interventions that can be integrated into pre-existing techniques as well as clear descriptions of how to do so. The term "small teaching" refers to an approach that seeks to spark positive change in the classroom through small but powerful modifications to course design and teaching practices. A small teaching approach or activity may take one of three forms: brief classroom or online learning activities, one-time interventions in a course, or small modifications in course design or communication with students. Each chapter introduces a basic concept in cognitive research that has implications for classroom teaching, explains the rationale for offering it within a specific time period in a typical class, and then provides concrete examples of how this intervention has been used or could be used by faculty in a variety of disciplines. The second edition will feature 20% revised and updated content, including a newly authored preface, updated examples and specific techniques, updated research, a new "self-explanation" chapter, and updated resources."--